Argonaute proteins are key determinants of RNAi efficacy, toxicity, and persistence in the adult mouse liver - Grimm, Dirk (American Society for Clinical Investigation, 2010)
shRNA overexpression from viral gene therapy vectors can trigger cytotoxicity leading to organ failure and lethality in mice and rats. This process likely involves saturation of endogenous cellular RNAi factors including exportin-5 (Xpo-5). Here, we have shown that Xpo-5 overexpression enhanced shRNA efficiency in the liver of adult mice but increased hepatotoxicity. We identified the 4 members of the human Argonaute (Ago) protein family as downstream factors involved in saturation of endogenous cellular RNAi, all of which were able to interact with shRNAs in cells and mice. In Ago/shRNA coexpression studies, Ago-2 (Slicer) was the primary rate-limiting determinant of both in vitro and in vivo RNAi efficacy, toxicity, and persistence. In adult mice, vector-based Ago-2/Xpo-5 coexpression enhanced U6-driven shRNA silencing of exogenous and endogenous hepatic targets, reduced hepatotoxicity, and extended RNAi stability by more than 3 months. Use of weaker RNA polymerase III promoters to minimize shRNA expression likewise alleviated in vivo toxicity and permitted greater than 95% persistent knockdown of hepatitis B virus and other transgenes in mouse liver for more than 1 year. Our studies substantiate that abundant small RNAs can overload the endogenous RNAi pathway and reveal possible strategies for reducing hepatotoxicity of short- and long-term clinical gene silencing in humans.